1988
DOI: 10.1177/030006058801600610
|View full text |Cite
|
Sign up to set email alerts
|

Deep Vein Thrombosis of the Legs: New Therapy by Mean of Low Molecular Weight Heparins

Abstract: This open controlled study compared the effects of subcutaneous administration of two types of heparin in two groups of 40 patients each with deep vein thrombosis. One group received calcium heparin and the other received low molecular weight heparin for 40 days in each case. Patients receiving low molecular weight heparin showed a greater increase in inhibition of activated factor X than those receiving calcium heparin. Both drugs slightly reduced activated partial thromboplastin time. No patient experienced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Twenty‐six randomized controlled trials were identified from the bibliographic search by following the methodology previously described in Study identification (above) [5–30]. All of them compared the efficacy of UFH and LMWH in patients with DVT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty‐six randomized controlled trials were identified from the bibliographic search by following the methodology previously described in Study identification (above) [5–30]. All of them compared the efficacy of UFH and LMWH in patients with DVT.…”
Section: Resultsmentioning
confidence: 99%
“…All of them compared the efficacy of UFH and LMWH in patients with DVT. Ten clinical trials with no venographic assessment [21–30], and three trials with a follow‐up period of < 2 months [5–7] were excluded. Finally, 13 randomized controlled clinical trials were included [8–20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 22 randomized studies that fulfilled our inclusion criteria were identified, where LMWH was compared with UFH for the initial treatment of VTE. [3][4][5][6][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Twelve studies were excluded for the following reasons: inadequate or incomplete follow-up or the inavailability of 3-month mortality figures for cancer patients [21][22][23][24][25][26][27][28][29][30] ; duplicate report 31 ; or because the study was primarily a dose-finding study 32 . The recently published study by Decousus and colleagues was also excluded because of its factorial study design and the absence of cancer patient-specific data in the main article.…”
Section: Meta-analysismentioning
confidence: 99%
“…The following LMW heparins have been investi gated and compared with unfractionated heparin for the treatment of DVT in prospective and randomized stud ies: nadroparin (Fraxiparin, Sanofi Winthrop), 6,7 CY 222 (Sanofi Winthrop), 8 dalteparin (Fragmin, Pharma cia Upjohn), [9][10][11][12][13][14][15][16] enoxaparin (Clexane, Rhone Poulenc Rorer), 4,5,17-20 certoparin (Mono-Embolex, Sandoz), 2122 logiparin (Innohep, Braun Melsungen), 23,24 and OP 2123 (Fluxum, Alfa Wassermann). [25][26][27] An overview of the studies and their treatment groups until June 1996 is given in Table 3.…”
Section: Treatment Of Dvt With Lmw Heparinmentioning
confidence: 99%